Returns to School Spending in Rural America: Evidence from Wisconsin's Sparsity Aid Program - Riley Acton; Cody Orr; Salem Rogers (Institute of Labor Economics (IZA), 2023)
We study the effects of increased school spending in rural American school districts by leveraging the introduction and subsequent expansion of Wisconsin's Sparsity Aid Program. We find that the program, which provides additional state funding to small and isolated school districts, increased spending in eligible districts by 2% annually and that districts primarily allocated funds to areas with low baseline budget shares. This increased spending has little effect on standardized test scores, but modestly increases college enrollment and completion for students with a low likelihood of attending or completing college.
Keywords: H75; I21; I22; R51; 330; school finance; educational attainment; rural schools